Carwash Station Prototype with Automatic Payment Using Intelligent Control Systems - Buele, Jorge (2021)
The daily activities of human being can be improved with the use of technology. Therefore, in this work we propose the design of an imperative system of automatic payment to prevent contact between people, avoiding the transmission of viruses and bacteria. Thus, new appropriate and innovative tools are created and applied to business models for the industrial and service sectors. Using and integrating communication between visual programming platforms, telecommunications (messaging) and online payments, using a programmable automaton, an HMI and a Raspberry board. The results show a robust platform framed in electronic payment technology with high performance and very reliable that uses the MQTT protocol for communication. The results show a time of 2.07 s in data writing after sending the signal and 0.80 s of reading the PLC outputs to the monitoring page